An RF switching circuit using PIN diode for a 2.4GHz frequency reconfigurable antenna - Nurul Hazlina, Noordin; Hwa, L. B.; N., Hassan; Rosdiyana, Samad; Zuwairie, Ibrahim (IEEE, 2018)
This paper discusses the design of an RF switching using PIN diode for a 2.4GHz polarization reconfigurable antenna. The PIN diode in a switching circuit requires an accompanying PIN diode driver or switch driver that provides a controlled forward bias current and a reverse bias voltage. The 2.4GHz polarization reconfigurable antenna is able to switch between Linear Polarization (LP), Left Hand Circular Polarization (LHCP) and Right Hand Circular Polarization (RHCP). The RF switching circuit includes PIN diode, RF choke inductor and DC block capacitor. The antenna also demonstrates good matching performance between the result of axial ratio and frequency for all polarization modes.